Taxation Challenges in Islamic Financial Instruments: Indonesian Regulatory Framework - Jamil, Hikmah; A'yun, Inarotul (Asian Journal of Law and Islamic Finance, 2025)
Indonesia, as the world’s largest Muslim-majority nation, faces significant taxation challenges in developing its Islamic finance sector despite government commitments to becoming a global Islamic economic center. This study examines the regulatory framework governing taxation of Islamic financial instruments in Indonesia, focusing on issues of tax neutrality, double taxation, and regulatory harmonization. Employing doctrinal legal analysis and comparative regulatory review, this research analyzes Indonesian tax regulations, fatwas from the National Sharia Board (DSN-MUI), and Financial Services Authority (OJK) regulations from 2008 to 2025. The principal findings reveal that Indonesia’s current tax framework creates competitive disadvantages for Islamic financial instruments compared to conventional products, particularly in sukuk issuance and murabahah financing, due to multiple transfer taxes and stamp duties. The study concludes that achieving tax neutrality requires comprehensive regulatory reform integrating Sharia principles with conventional tax law. Future research should examine the impact of proposed tax incentive schemes on market penetration of Islamic financial products. This research provides policy implications for Indonesian tax authorities to design equitable taxation frameworks that support Islamic finance growth while maintaining fiscal revenue. Managerially, Islamic financial institutions can utilize these findings to advocate for regulatory reforms and structure products more tax-efficiently.